Urgensi Altruisme Sebagai Ketahanan Sosial dalam Penanganan Bencana Covid-19: Studi Konseptual Terhadap Tingginya Egosentris Masyarakat Selama Pandemi - K.T., Angelus Vecky; Asmawati (Jounal Nyanadassana, 2024)
This article focuses on the altruism crisis that has emerged in society during the COVID-19 pandemic. This is proven by violators of health norms' carelessness to the risk of the infection spreading further. Those infected with the COVID-19 virus do so on purpose in public areas, oblivious to the consequences for others. This article also demonstrates that low empathy, social responsibility, and self-control influence the crisis of altruism experienced by health protocol violators, according to a literature review. As a result, we provide a scientific contribution by reminding society of the necessity of altruism in preventing the spread of the COVID-19 virus through this article.